CHARACTERISTICS OF INDIGENOUS CULTURE AND DISASTER MANAGEMENT OSING TRIBE, KEMIREN VILLAGE, GLAGAH DISTRICT, BANYUWANGI REGENCY - Mochammad Shofwan; Nasobi Niki Suma; Jelita Citrawati Jihan (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2022)
Banyuwangi has excellent potential in Tourism sector. One is Osing traditional tourism located in Kemiren Village, Glagah District. With the possibility of culture, that is still a perfect opportunity to introduce the original culture of Banyuwangi throughout Indonesia and even abroad. The method used in this study is descriptive qualitative data collection techniques used in the study of observation and documentation. The purpose of this study is to know and know the cultural customs and disasters of the Osing Tribe, Kemiren Village. The results of the analysis based on the calculation of IFAS and EFAS are known quadrant matrix is located in Quadrant I; this shows that the village Kemiren has a favorable situation which has an excellent opportunity to make the village Kemiren as a disaster-aware Tourism Village. Traditions such as Barong Ider Bumi, Tumpeng Sewu, drinking coffee, Angklung Paglak, Mocoan Lontar Yusuf, and sustainable traditional house systems can be significant forces to increase disaster mitigation capacity.